2011
DOI: 10.1177/1076029611418967
|View full text |Cite
|
Sign up to set email alerts
|

Generic Versus Branded Enoxaparin in the Prevention of Venous Thromboembolism Following Major Abdominal Surgery

Abstract: This exploratory trial suggests that the generic LMWH is probably as safe and as effective as the branded enoxaparin (Lovenox, Brazil) in the prophylaxis of VTE in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The 2% incidence of venous thromboembolism in both groups was low and not different between the groups. Thus, no definite conclusions could be drawn from this small study [33]. For patients with unstable angina it was reported that the safety and efficacy of biosimilar LMWHs may not be equivalent to the originator versions even if equivalence was shown in another clinical setting as outcomes of clinical trials cannot be extrapolated between different patient populations [34][35][36].…”
Section: Clinical Trials For Biosimilar Lmwhsmentioning
confidence: 90%
“…The 2% incidence of venous thromboembolism in both groups was low and not different between the groups. Thus, no definite conclusions could be drawn from this small study [33]. For patients with unstable angina it was reported that the safety and efficacy of biosimilar LMWHs may not be equivalent to the originator versions even if equivalence was shown in another clinical setting as outcomes of clinical trials cannot be extrapolated between different patient populations [34][35][36].…”
Section: Clinical Trials For Biosimilar Lmwhsmentioning
confidence: 90%
“…There was a difference in AHPF4 antibodies for the biosimilar, but the authors made no conclusions what should be the consequence of this finding . Another explorative trial with the same Brazilian enoxaparin in 200 patients with venous thromboembolism showed no difference in effect . The pharmacovigilance of biosimilars in the European has not yet lead to safety signals…”
Section: Methodsmentioning
confidence: 98%
“…28 Another explorative trial with the same Brazilian enoxaparin in 200 patients with venous thromboembolism showed no difference in effect. 29 The pharmacovigilance of biosimilars in the European has not yet lead to safety signals. 30 Specific attention on the occurrence of HIT should be a more prominent part of the discussion.…”
Section: Clinical Aspects Of Lmwhs With Special Attention For Hitmentioning
confidence: 99%
“…Among the enoxaparin studies (n = 9), the largest examining clinical outcomes compared Lovenox with a generic version produced by Eurofarma (the study was also funded by Eurofarma) [22]. Among the 200 post-surgical patients analyzed in a randomized, prospective fashion, the authors found no differences in clinical endpoints and laboratory measures of anticoagulant activity.…”
Section: Studies Of Non-fda-approved Generic Versionsmentioning
confidence: 98%